2016
DOI: 10.1212/wnl.0000000000003327
|View full text |Cite
|
Sign up to set email alerts
|

Thalamo-cortical network activity during spontaneous migraine attacks

Abstract: We used MRI to search for changes in thalamo-cortical networks and thalamic microstructure during spontaneous migraine attacks by studying at the same time structure with diffusion tensor imaging and resting state function in interconnected brain networks with independent component analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 41 publications
6
81
0
Order By: Relevance
“…Our findings are particularly interesting in this population, 23,24 since thalamocortical network dysfunction, 25,26 thalamic microstructural changes, 27,28 and thalamic morphological abnormalities 29 have been recently demonstrated in individuals with migraine. Migraine is a disorder that is frequently clinically and radiographically mistaken for MS, 5,6 and previous studies have also suggested an increased risk of migraine in patients with MS. 30 In our MS + c cohort, 6/10 participants had migraine.…”
Section: Discussionmentioning
confidence: 62%
“…Our findings are particularly interesting in this population, 23,24 since thalamocortical network dysfunction, 25,26 thalamic microstructural changes, 27,28 and thalamic morphological abnormalities 29 have been recently demonstrated in individuals with migraine. Migraine is a disorder that is frequently clinically and radiographically mistaken for MS, 5,6 and previous studies have also suggested an increased risk of migraine in patients with MS. 30 In our MS + c cohort, 6/10 participants had migraine.…”
Section: Discussionmentioning
confidence: 62%
“…There are also studies that found no differences between migraine patients and healthy controls. These studies employed methods whole-brain such as TBSS [22,56], ROI-based analysis (ictal migraine) [57] and voxel-based whole brain comparison [58]. Interestingly, the trend when comparing AD values between EM and healthy controls is inverted when comparing CM and healthy controls or CM with respect to EM (Additional file 1: Figures S4 and S5).…”
Section: Discussionmentioning
confidence: 99%
“…The increased sensitivity is consistent with the reports of the cortex being hyperexcitable in migraine. [6][7][8][9][10] Further evidence of cortical hyper-excitability in migraine is based on the reduced thresholds for inducing phosphenes with stimulation methods, 29,30 the co-morbidity of migraine and epilepsy, and the use of anti-seizure medication 31 ). The increased ERP amplitude in migraine, however, was not consistently larger across the visual cortex compared to controls.…”
Section: Large and Large Chromaticity Separations For Individuals Wimentioning
confidence: 99%